The Millenial Use Of Mental Health Service Instagram Account, @RILIV, In Surabaya - Kadek Sharidevy Anggira Gashya; Syifa Syarifah Alamiyah (Jurnal Ilmu Komunikasi, 2019)
Recently health information is widely discuses on Internet platforms.Include on Instagram, as image sharing social media platforms. This study exploreshow millennial generation in Surabaya use Instagram platform, which discussedmental health issues. This study employs descriptive qualitative method to describethe experiences of the informants and their motives. Object of the study are aged18-25 years. Data gained through in-depth interview and observation, andanalysed based on the emerging theme. This study concludes that millennialSurabaya use Instagram to see mental health information as weekly basis, they tendto see Instagram with interesting content and attractive design, some of thepreferred contents are self love, self harm, body positivity and others. Reliability ofthe platform, motives and impact are also discusses in this article.